La ville, la salle, la scène : les Siennoises et le théâtre - Marie-Françoise Piéjus (Etudes Epistémè)
In the sixteenth century the Academy of the Intronati produced romantic comedies in Siena, which were rooted in contemporary reality. These comedies quickly became famous throughout Italy and abroad. These festivals were officially offered to the noble ladies of the city because the academicians wanted to remain faithful to the courtly ideal evoked in Castiglione’s treatise. Sienese women’s taste for the theatre and their participation in private performances is well-known. Their fame in the intellectual field is attested by the dedications they received, the poems they composed, the writings that praised their qualities of mind and culture. The actor who says the prologue praises their beauty, while using an equivocal language that is full of innuendoes. Such performances also answer the diplomatic needs of the small republic, which was forced to honor the powerful ones who threatened its political destiny. In order to honor ladies, the plot highlights heroines who, despite tribulations inspired by Alexandrian novels, affirm their fidelity to the man they love, and the comedies end with love marriages, offering to female spectators a utopian vision of their condition. However, this moralistic scheme suggests a strong erotic tension in male/female relationships. The performance also relies on the traditional satire of women's shortcomings, which is a tried-and-tested comic device, as academic dignity must bend to the requirements of the stage and deal with the prejudices of everyday life. The female spectators are thus invited to laugh, if not at their own image, at least at the weaknesses of women.